HBR's 10 must reads. Vol. 2 : on strategy. (Boston, Massachusetts : Harvard Business Review Press, 2020)
"Do you have the right strategy to lead your company into the future? More of the ideas you want, from the authors you trust. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you combat new competitors and ensure that you can define--and execute--the best strategy for your company. With insights from leading experts, this book will inspire you to: choose a strategy that best meets the demands of your competitive environment, generate economic value for your company, while also producing value for society, create and capture new markets--and break free of old ones, see the growing relevance of data analytics in your organization, transform your products and services into platforms, identify the signals of future disruption and take steps to avoid it. HBR's 10 Must Reads paperback series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their companies, should look no further. HBR's 10 Must Reads series focuses on the core topics that every ambitious manager needs to know: leadership, strategy, change, managing people, and managing yourself. Harvard Business Review has sorted through hundreds of articles and selected only the most essential reading on each topic. Each title includes timeless advice that will be relevant regardless of an ever-changing business environment"--
Your strategy needs a strategy / by Martin Reeves, Claire Love, and Philipp Tillmanns -- Transient advantage / by Rita Gunther McGrath -- Bringing science to the art of strategy / by A.G. Lafley, Roger L. Martin, Jan W. Rivkin, and Nicolaj Siggelkow -- Managing risks: a new framework / by Robert S. Kaplan and Anette Mikes -- Surviving disruption / by Maxwell Wessel and Clayton M. Christensen -- The great repeatable business model / by Chris Zook and James Allen -- Pipelines, platforms, and the new rules of strategy / by Marshall W. Van Alstyne, Geoffrey G. Parker, and Sangeet Paul Choudary -- Why the lean start-up changes everything / by Steve Blank -- Strategy needs creativity / by Adam Brandenburger -- Put purpose at the core of your strategy / by Thomas W. Malnight, Ivy Buche, and Charles Dhanaraj -- Creating shared value / by Michael E. Porter and Mark R. Kramer.
Includes index.
Keywords: Strategic planning